(untitled) (African Journal of Biomedical Research, 2024)
Marital Rape (MR) has long been categorized as a serious societal issue and public health problem which affects many women with several physically, emotional, psycho-social and reproductive consequences. Despite the reality and severity of MR, it has received limited attention in scholarly research in Nigeria since the existence of rape in intimate relationship is being doubted. This study, therefore, examined the perspectives on Marital Rape (MR) among women in Oyo State, Nigeria. The study employed an exploratory qualitative approach to data collection. Data were collected using a pretested Focus group discussion guide (FGD) that explored the perceptions of various issues including the reality, seriousness, threat, health burden, determinants and reporting of MR. A total of twelve FGDs were conducted among 87 purposively selected ever-married women aged 18 – 60 years drawn from three major cities in Oyo State, Nigeria. Data were audio-taped, transcribed, and analyzed thematically. Participants commonly condemned MR and considered it an aberration. Participants mentioned various consequences of MR including bodily injuries and depression. Perceived determinants of MR included women indulgence in extra-marital affairs, psychoactive-drugs use by husbands, turning down of husbands’ sexual request and economic dependence on husbands. It was perceived that women rarely report their experiences due to psycho-social factors including fear of stigmatization and self-blame. Multiple public health education interventions including advocacy and social support are needed to address the phenomenon.